Education and the Spirit of Man - Pollard, Francis E. (London George Allen & Unwin LTD)
This volume was the Swarthmore Lecture for 1932, one of an annual series of lectures delivered by and for members of the Society of Friends (Quakers). The lecture discusses the place of education and moral philosophy in the world of the early twentieth century, as well as the place of religious discipline in education.
Keywords: Moral education -- Society of Friends--Education